PROFIL PEREMPUAN USAHA KECIL DI SURAKARTA - Endang Sri Sudalmi (Innofarm:Jurnal Inovasi Pertanian, 2009)
ABSTRACT The aim of this research is to know the profile of female micro entrepreneur in Surakarta. This research used quantitative approach method and qualitative female point of view approach method. The data used are main data and supporting data. Descriptive data analytical technique – explanation: The result of this research shows:1. The average period of the entrepreneurships is ten years. Most of them are inherit from their ancestor. 2. All of the respondents share the same experience of failure, but then they reconstructed their business after all. In running their business, those entrepreneurs get some helps from their co-workers. Those co-workers are paid daily.There are some general barriers faced in running their business; difficulties in gaining the capital, difficulties in finding the well skilled employees, difficulties in finding the raw materials, and the great numbers of the competitor.All of the respondents include in a female micro entrepreneur networking and they feel many advantages from this networking system.It is seen that the pattern put the female and male achiever in the same position and responsibility. Since those kinds of business are home industries, therefore the financial issue should be separated between business financial and family financial.  It is shown also that the average income earning can reach the number of 1 million Rupiah per month.The entrepreneurs get PUK supervision from formal organizations such as LSM Ngudi Lestari, LPTP, ASPUMKM and KOPERASI from the DKRPP-KB government, KOPERASI affairs ministry, INDUSTRIAL ministry, and COMMERCE ministry. The entrepreneurs get the same facilities. They are; supervision in technique and management practicing, entrepreneurship consultation, and even capital lending from the government. The gathering is held once in a month. Keywords : female micro entrepreneur, networking, and supervision.